PENGGUNAAN MEDIA BIG BOOK UNTUK MENINGKATKAN KEMAMPUAN MEMBACA PEMAHAMAN PESERTA DIDIK KELAS III SDN TERUSAN 1 SINDANG INDRAMAYU : media - ida faridah, Hani Fita Fatimah; Erna Labudasari; Nurkholis (Pendas : Jurnal Ilmiah Pendidikan Dasar, 2025)
This study aims to improve the reading comprehension skills of third-grade students at SDN Terusan 1 Sindang Indramayu through the use of Big Book media. The research was motivated by the low level of reading comprehension among students, as indicated by the pre-cycle evaluation, where only 49% of students met the minimum passing criteria. The objectives of this studr are to explore the planning, implementation, and impact of using Big Book media in reading comprehension learning. The research method used is Classroom Action Reseatch (CAR) based on the Kemmis and McTaggart model, which consists of four stages: planning, action, observasion, ang reflection. Data were collecred through observation, interviews, documentation, and comprehension tests. The results demonstrated a significant improvement in students’ reading comprehension abilities. In the first cycle, the percentage of students who met the learning mastery criteria increased to 74%, and in the second cycle, it rose to 91%. These improvements were observed in students’ ability to identify main ideas, answer explicit question, and engaging learning experience, encouraging students to participate actively in reading activities. Based on the findings, it can be concluded that big book media is an effective and innovative tool to enhance reading comprehension skills in elementary school students.